Highly Elevated Serum Hepcidin in Patients with Acute Myeloid Leukemia prior to and after Allogeneic Hematopoietic Cell Transplantation: Does This Protect from Excessive Parenchymal Iron Loading?. (14th April 2011) - Eisfeld, Ann-Kathrin; Westerman, Mark; Krahl, Rainer; Leiblein, Sabine; Liebert, Uwe Gerd; Hehme, Marianne; Teupser, Daniel; Niederwieser, Dietger; Al-Ali, Haifa Kathrin
Abstract : Hepcidin is upregulated by inflammation and iron. Inherited (HFE genotype) and treatment-related factors (blood units (BU), Iron overload) affecting hepcidin (measured by C-ELISA) were studied in 42 consecutive patients with AML prior to and after allogeneic hematopoietic cell transplantation (HCT). Results . Elevated serum ferritin pre- and post-HCT was present in all patients. Median hepcidin pre- and post-HCT of 358 and 398 ng/mL, respectively, were elevated compared to controls (median 52 ng/mL) (P < .0001 ). Liver and renal function, prior chemotherapies, and conditioning had no impact on hepcidin. Despite higher total BU after HCT compared to pretransplantation (P < .0005 ), pre- and posttransplant ferritin and hepcidin were similar. BU influenced ferritin (P = .001 ) and hepcidin (P = .001 ). No correlation of pre- or posttransplant hepcidin with pretransplant ferritin was found. HFE genotype did not influence hepcidin. Conclusions . Hepcidin is elevated in AML patients pre- and post-HCT due to transfusional iron-loading suggesting that hepcidin synthesis remains intact despite chemotherapy and HCT.